Determining factors of user satisfaction in health centers: Role of service quality - Espinoza Orellana, Mónica Elizabeth (REDIELUZ, 2024)
User satisfaction is considered as an attitudinal response and value judgment that the user generates after encountering or interacting with the service. Objective: identify the factors that most frequently influence user satisfaction in health centers. Method: Descriptive research with documentary, retrospective, non-experimental design. Through a review of the literature available in different search engines such as Elsevier, Pubmed, Scielo and Google Scholar. Those articles from the last eight years were prioritized. 8 articles were selected from the various databases. Results and Discussion: from a multidimensional perspective, various factors that influence satisfaction have been grouped, these include individual factors, factors related to care characteristics, factors related to communication during admission and family/social factors. Conclusions: Satisfaction with health services is a multidimensional concept that is influenced by subjective factors, such as previous experiences, future expectations and the user’s social context. This complexity makes its analysis difficult, but also highlights its importance as a tool to generate information that optimizes the management of health resources and responds more effectively to the needs of patients.